Przemiany w spożyciu żywności w wybranych krajach CEFTA - Borowska, Agnieszka; Zajączkowska, Maria (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
In the period of political and economic transformation, the countries of Central and Eastern Europe belonging to the CEFTA showed similar tendencies in food consumption in spite of its different level per capita in the selected countries. The changes in food consumption observed in Romania are essentially less dynamic in comparison with the CEFTA other countries. Generally, all examined countries experienced a decline - in quantity terms - in consumption of red meat, animal fat, cereal products, potatoes and sweets. The increased consumption was noted in the case of poultry meat, vegetable fats and oils, fish and fruits. Observed changes in food consumption in investigated countries are close to tendencies existing in developed countries of the EU in the fifties and sixties as well as in Greece, Spain and Portugal in the eighties and in the nineties.